Respuesta :
Answer:
- (x + 3)(x - 3)(x² - 2x + 5)
Step-by-step explanation:
One of the zeros given:
- 1 + 2i
Since it is a complex number, its conjugate is also a zero:
- 1 - 2i
The product of two factors are:
- (x - (1 + 2i))(x - (1 - 2i)) =
- x² - x(1 + 2i + 1 - 2i) + (1 - 4i²) =
- x² - 2x + 5
We need two more zeros. Let them be m and n, then we have:
- (x - m)(x - n) = x² - (m +n)x + mn
The product of all factors:
- (x² - 2x + 5)(x² - (m+n)x + mn) = x⁴ - 2x³ - 4x² + 18x - 45
- x⁴- (m+n+2)x³ + (mn+5)x² - (2mn+5m+5n)x + 5mn = x⁴- 2x³- 4x²+ 18x- 45
Compare left and right sides and solve for m and n:
- m + n + 2 = 2 ⇒ m + n = 0
- mn + 5 = -4 ⇒ mn = -9
- 2mn + 5(m + n) = -18 ⇒ mn = -9
From the above equations we get:
- m = -n
- -n² = -9
- n = 3
- m = -3
The other zero's are 3 and -3
All of the factors:
- (x + 3)(x - 3)(x² - 2x + 5)
Answer:
(x−3)(x+3)(x^2-2x+5)
Step-by-step explanation:
f(x) = x^4 - 2x^3 - 4x^2 + 18x - 45
To factor the expression, solve the equation where it equals to 0.
x^4 - 2x^3 - 4x^2 + 18x - 45 = 0
By Rational Root Theorem, all rational roots of a polynomial are in the form p/q where p divides the constant term −45 and q divides the leading coefficient 1. List all candidates p/q.
±45,±15,±9,±5,±3,±1
Find one such root by trying out all the integer values, starting from the smallest by absolute value. If no integer roots are found, try out fractions.
x=3
By Factor theorem, x−k is a factor of the polynomial for each root k. Divide x^4 - 2x^3 - 4x^2 + 18x - 45 by x−3 to get x^3 + x^2 - x + 15. To factor the result, solve the equation where it equals to 0.
x^3 + x^2 - x + 15 = 0
By Rational Root Theorem, all rational roots of a polynomial are in the form p/q where p divides the constant term 15 and q divides the leading coefficient 1. List all candidates p/q.
±15,±5,±3,±1
Find one such root by trying out all the integer values, starting from the smallest by absolute value. If no integer roots are found, try out fractions.
x=−3
By Factor theorem, x−k is a factor of the polynomial for each root k. Divide x^3 + x^2 - x + 15 by x+3 to get x^2 - 2x + 5. To factor the result, solve the equation where it equals to 0.
x^2−2x+5=0
All equations of the form ax^2 + bx + c=0 can be solved using the quadratic formula: −b±√b2-4ac/2a. Substitute 1 for a, −2 for b, and 5 for c in the quadratic formula.
x=-(-2)+√(-2)^2 - 4 x 1 x 5 / 2
Do the calculations.
x=2+√-16 / 2
Polynomial x^2−2x+5 is not factored since it does not have any rational roots.
x^2−2x+5
Rewrite the factored expression using the obtained roots.
(x−3)(x+3)(x^2-2x+5)